Longitudinal blood pressure and body mass index in South African adolescents - van Niekerk, Elandi; Kruger, Ruan; Sedumedi, Caroline; Brits, Sanette J.; Monyeki, Makama Andries (Frontiers in Pediatrics, 2025)
AimBlood pressure (BP) is known to be affected by body mass index (BMI) from an early age, but research in South African youth is scarce. We assessed longitudinal trends and relationships between BP measures and BMI in a South African adolescent cohort.Materials and methodsThis longitudinal study (2010–2014) included 121 South African adolescent boys and girls of Black and White ethnicity from the Physical Activity Health Longitudinal Study. Measures included systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure, mid-blood pressure (Mid-BP), mean arterial pressure (MAP), and BMI.ResultsOver four years, significant increases (p < 0.05) in BMI, SBP, DBP, PP, Mid-BP, and MAP were observed in adolescents (p < 0.001). BMI was consistently and positively associated with various BP measures across the study period. In 2012, BMI associated with SBP (β = 0.22; p = 0.018), DBP (β = 0.22; p = 0.018), Mid-BP (β = 0.24; p = 0.009), and MAP (β = 0.24; p = 0.009). These associations persisted in 2013, with stronger relationships observed for SBP (β = 0.27; p = 0.003), DBP (β = 0.21; p = 0.030), Mid-BP (β = 0.27; p = 0.004), and MAP (β = 0.27; p = 0.005). In 2014, BMI associated with Mid-BP (β = 0.22; p = 0.017) and MAP (β = 0.23; p = 0.015). After adjusting for the previous year's BP, BMI positively associated with SBP (β = 0.23; p = 0.013) in 2013 and DBP (β = 0.19; p = 0.049) in 2014. Significant associations remained between BMI and Mid-BP (β = 0.18–0.21; p = 0.022–0.047) and MAP (β = 0.19–0.20; p = 0.028–0.045) across 2012 and 2013.ConclusionCumulatively increasing BP significantly and positively associated with BMI, suggesting that increasing BMI may contribute to elevated BP during adolescence. Early identification and targeted lifestyle interventions are required to mitigate obesity-related elevated BP in South African adolescents.